2020
DOI: 10.3390/s20205871
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized TiO2 Nanotube-Based Electrochemical Biosensor for Rapid Detection of SARS-CoV-2

Abstract: The COronaVIrus Disease (COVID-19) is a newly emerging viral disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Rapid increase in the number of COVID-19 cases worldwide led the WHO to declare a pandemic within a few months after the first case of infection. Due to the lack of a prophylactic measure to control the virus infection and spread, early diagnosis and quarantining of infected as well as the asymptomatic individuals are necessary for the containment of this pandemic. Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 32 publications
1
125
0
2
Order By: Relevance
“…The limit of detection of this sensor for the detection of the SARS-CoV-2 spike protein was 0.7 nM. This electrochemical-based biosensor can be used to detect SARS-CoV-2 in nasal, nasopharyngeal swabs, and saliva samples [60].…”
Section: Electrochemical Biosensingmentioning
confidence: 98%
“…The limit of detection of this sensor for the detection of the SARS-CoV-2 spike protein was 0.7 nM. This electrochemical-based biosensor can be used to detect SARS-CoV-2 in nasal, nasopharyngeal swabs, and saliva samples [60].…”
Section: Electrochemical Biosensingmentioning
confidence: 98%
“…However, the as suggested biosensor required a relatively high analysis time close to 30 min, which should be ameliorated with further research.
Figure 7 Voltammogram of: (Ai) S-protein detection and (Aii) P-protein detection [97] ; (Bi) TiO 2 nanotubes functionalized by Co (Co-TNTs), as electrode material for a SARS-CoV-2 biosensor; (Bii) Linear response for concentration range between 14 nM to 1400 nM and a detection response time of ∼30 sec [102] ; (Ci) Schematic illustration of –NH 2 groups of the SARS-CoV-2 proteins or antibodies attached to 1-Pyrenebutyric acid (PBA); (Cii) Current response of real samples detection of the N-proteins, S1-IgG, S1-IgM and CRP [103] ; (Di) FET SARS-CoV-2 biosensor; (Dii) For laboratory sample the lower limit of detection of SARS protein, was recorded at 1 fg/mL and 100 fg/mL [104] . Reproduced with permission.
…”
Section: Carbon and Graphene-based Sars-cov-2 Electrochemical Biosensorsmentioning
confidence: 99%
“…The titania nanotubes functionalization with Co ( Fig. 7 Bi), adopted by Vadlamani et al [102] , was the key element for ensuring: i) stability and selectivity of the novel SARS-CoV-2 biosensor and ii) successful immobilization of SARS-CoV-2 spike protein molecules. As the authors observed [102] , the functionalization of the catalyst improved three main characteristics of the sensor: i) its selectivity towards the S-Receptor Binding Domain (SRBD) protein, ii) its sensitivity, showing a linear response in the concentration range between 14 nM to 1400 nM and iii) its response time (30 sec) ( Fig.…”
Section: Carbon and Graphene-based Sars-cov-2 Electrochemical Biosensorsmentioning
confidence: 99%
“…However, this biosensors typology shows a limited shelf life, and a sensitivity affected by sample matrix and temperature, inducing the antibodies deterioration, thus corrupting the sensor operation. The plasmonic biosensors are very sensitive to small sample changes and repeatable, as well as do not require a calibration model given to the conventional electrical model (Villena Gonzales et al, 2019). However, they are susceptible to motion, temperature, and sweat, and need a long calibration process.…”
Section: Performance and Comparative Analysis Of Discussed Systems Smentioning
confidence: 99%